2020
DOI: 10.1111/hepr.13467
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of liver stiffness measurement before and after direct‐acting antiviral therapy to predict hepatocellular carcinoma and exacerbation of esophageal varices in chronic hepatitis C

Abstract: Aim: The risk of development of hepatocellular carcinoma (HCC) persisted in patients with advanced fibrosis, even after achieving sustained virologic response (SVR). This study aimed to show the advantage of liver stiffness measurement (LSM) at baseline and after SVR to predict HCC occurrence and esophageal varices (EV) exacerbation.Methods: These risks were evaluated in 398 chronic hepatitis C patients without a history of HCC who achieved SVR after directacting antiviral agent and evaluated LSM at least twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…Ogasawara et al . reported that liver stiffness at 24 weeks after EOT is a predictor for esophageal varices exacerbation after achieving SVR in patients with HCV‐related cirrhosis 36 . Measurement of liver stiffness before or after DAA therapy also seems to be advisable to predict the aggravation of EGV.…”
Section: Discussionmentioning
confidence: 99%
“…Ogasawara et al . reported that liver stiffness at 24 weeks after EOT is a predictor for esophageal varices exacerbation after achieving SVR in patients with HCV‐related cirrhosis 36 . Measurement of liver stiffness before or after DAA therapy also seems to be advisable to predict the aggravation of EGV.…”
Section: Discussionmentioning
confidence: 99%
“…From a report on the histological analysis of the resected liver, in patients who underwent liver resection due to HCC after an SVR, the liver stiffness measured by TE improved to the normal range, although histological fibrosis was evident as F4-cirrhosis [61]. A longitudinal analysis from Japan on liver stiffness before and after DAA showed that liver stiffness measurements decreased after an SVR24, while patients who developed HCC maintained higher liver stiffness than others [62]. In patients with higher liver stiffness, fibrosis-related activated hepatic stellate cells may be present; these cells produce cytokines, such as transforming growth factor (TGF)-β, which plays a prometastatic role in HCC by inducing epithelial-mesenchymal transition (EMT) [63].…”
Section: Hcv-related Chronic Hepatitis Recent Advances In the Managemmentioning
confidence: 99%
“…Baseline LSM obtained by Acoustic Radiation Force Impulse (ARFI) or TE, was associated with an increased risk of post-treatment HCC ( Table 5 ) in three studies analysing SVR patients. 53 , 56 , 57 Tachi et al identified the 1.73 m/s threshold as the optimal cut-off to stratify CHC patients according to their de-novo HCC risk 56 ( Table 5 ). In the other two studies, baseline LSM ≥20 kPa and ≥17.5 kPa were associated with HCC occurrence in 398 and 773 CHC patients from Japan and Denmark, respectively.…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%